Preparation and Evaluation of Capsule Shell Films Formulated from Brown Seaweed Alginate (Sargassum crassifolium) - Baiq Vera El Viera; Syumillah Saepudin; Luthfiyah Irbah As Saidah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Brown seaweed (Sargassum crassifolium) grows a lot along the coast of Indonesia, especially in the Pangandaran area. Brown seaweed may serve as a viable natural source of sodium alginate, a biopolymer extensively utilized in pharmaceutical dosage forms. Most capsule shells are made of gelatin, but as more people seek alternatives to animal products, alginate-based materials are being explored. This study aimed to extract sodium alginate from Sargassum crassifolium and fabricate capsule-shell films, subsequently evaluating their physicochemical properties. To obtain sodium alginate powder, the extraction process involved the following steps: acid pretreatment, alkaline immersion, sodium carbonate extraction, bleaching, precipitation, and drying. The extracted material had a moisture content of 12% and a yield of 26.21%. FTIR spectroscopy confirmed the structure of the extracted material by showing that its functional groups, such as hydroxyl, carbonyl, C–O–H, and C–O–C, were the same as those of standard sodium alginate. Capsule-shell films were prepared by varying the alginate concentration in the casting volume to 3%, 4%, and 5%. Organoleptic testing showed that all formulations produced films that were slightly brown, opaque, and felt like paper. Tests on thickness and weight showed that films with higher alginate concentrations were thicker and heavier. F3-1 had a thickness value that was closest to what is needed for commercial hard capsules, and F1-2 had a moisture content range that was acceptable for commercial capsule shells. The moisture content of the formulations ranged from 8% to 24%, depending on the temperature, humidity, and length of time they were dried. All formulations produced films that could be used, but F3-1 had the best thickness, and F1-2 had the correct moisture content, supporting their potential application as non-gelatin capsule-shell alternatives.